Volatile Compounds Content, Physicochemical Parameters, and Antioxidant Activity of Beers with Addition of Mango Fruit (Mangifera Indica) - Alan Gasiński; Joanna Kawa-Rygielska; Antoni Szumny; Anna Czubaszek; Justyna Gąsior; Witold Pietrzak (Molecules, 2020)
This study was performed to determine the possibility of using mango fruit (Mangifera indica) in brewing technology. The aim of using the SPME-HS-GC-MS technique was to assess what changes occurred in the volatile composition of mango beers brewed in this study. Mango fruit was added to the beer in five different forms to ascertain what kind of preparation should be used to improve beer aroma. Analysis of the volatile components in mango beer showed that beer without mango addition was characterized by the lowest content of volatile compounds (1787.84 µg/100 mL). The addition of mango fruit increased the concentration of compounds, such as α-pinene, β-myrcene, terpinolene, α-terpineol, cis-β-ocimene, caryophyllene, and humulene, in beer. Beer prepared with mango pulp addition was characterized by the highest concentration of volatile components from mango beers (2112.15 µg/100 mL). Furthermore, beers with mango addition were characterized by a higher polyphenol content (up to 44% higher than control beer) and antioxidant activity than control beer and were evaluated by a trained panel as having a better taste and aroma than beer without fruit addition.